Response of maize genotypes to gray leaf spot disease (Cercospora zeae-maydis) in the hills of Nepal - Manandhar, G; Ferrara, GO; Tiwari, TP; Baidya, S; Bajracharya, ASR; Khadge, BR; Narro, L (Agronomy Journal of Nepal, 2013)
Gray leaf spot (GLS) is an important and destructive disease of maize in the hills of Nepal. The occurrence of this disease is recorded for the first time in the country in 2006. Several genotypes of maize supposed to be resistant to gray leaf spot in SARMP Zimbabwe and CIAT Colombia were evaluated together with other varieties in observation nursery conducted at farmer’s fields as well as at Khumaltar (NARC research station in the Kathmandu Valley) during 2008 and 2009. Ten out of 28 genotypes of maize were identified as resistant to moderately resistant to GLS. The disease incidence was higher on the open pollinated varieties of maize. The severity of GLS on genotypes of maize observed as 3.0 and 2.2, respectively at Baluwapati and Dhungkharka in Kavrepalanchwok and 2.0 at Khumaltar in Lalitpur during 2008. The severity of GLS was observed as high as 2.4 at Pakhribas in Dhankuta and 1.7 at Khumaltar in 2009. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7524 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.93-101